2016
DOI: 10.1007/s11832-016-0755-3
|View full text |Cite|
|
Sign up to set email alerts
|

Identifying non-accidental fractures in children aged <2 years

Abstract: PurposeFractures are the second most common presentation of child abuse following soft-tissue bruising and burns. It is often difficult to determine potential abuse in a child presenting with a non-rib fracture(s) and without soft-tissue injuries.MethodsOne hundred and fifteen consecutive patients aged ≤2 years who presented with a fracture between January 2010 and June 2012 to our emergency department (ED) or pediatric fracture clinic were retrospectively analyzed. Statistical analyses were carried out for no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 36 publications
1
26
0
Order By: Relevance
“…While some studies have suggested that NAT may be more common in males, others found that the rate of abuse was higher in African American children. Neither was a significant factor in this study [ 1 , 4 7 ]. We do concur with other studies that NAT most often occurs in children under the age of 2 [ 4 , 5 , 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…While some studies have suggested that NAT may be more common in males, others found that the rate of abuse was higher in African American children. Neither was a significant factor in this study [ 1 , 4 7 ]. We do concur with other studies that NAT most often occurs in children under the age of 2 [ 4 , 5 , 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…[7] Further, in a recent study, Leaman et al . [19] analyzed the data of 16 confirmed cases of abuse in children aged <2 years and found 13 (81%) children had multiple fractures. Nonetheless, a recent study from Singapore found multiple bone fractures to be rare, as it was reported in only 8.4% of the studied children.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in terms of fracture patterns, Leaman et al . [19] also found transverse fractures to be more common, with 8 of 11 femur fractures having the transverse fracture pattern. However, it should be noted that patterns do not significantly help guide a physician toward the suspicion of abuse,[13151617182122] likely because common fracture patterns are likely to differ.…”
Section: Discussionmentioning
confidence: 99%
“…12 Metaphyseal corner fractures, although highly specific for child abuse, may occur infrequently in the ambulatory child. 13 Repeat skeletal surveys may be performed in 2 weeks for high-risk cases. Bone scintigraphy may be used to complement radiographs when symptoms are poorly localized, particularly in nonverbal and/or neurodevelopmentally delayed children.…”
Section: Nonaccidental Traumamentioning
confidence: 99%